PENERAPAN ETIKA OLEH ORANG TUA TERHADAP ANAK DARI USIA DINI DEMI MEMBENTUK KARAKTER PADA ANAK DI PADANG REBA - Zeni Wulandari; Siregar, Zulham (Jurnal Berbasis Sosial, 2024)
This study aims to find out how the application of ethics carried out by parents in shaping character in children in Padang Reba. Ethics today has indeed changed a lot compared to the past due to the rapid development of the times. The application of ethics by parents is expected to be able to form character in children from an early age for the survival of children in the future. The lack of ethics in today's children makes researchers interested in researching the application of ethics by parents in children. Through a qualitative approach method with data collected through case studies, observations and interviews. The results of the study found that the role of parents is very important in shaping character in children. The example of parents is needed in educating children to form character in the child. A good and positive application will produce good results in the child's character. Parents must apply ethics as early as possible for a better future for their children, with strict supervision and good example and imparting ethical values will make children have quality character.